Evaluation of the effectiveness of physical exercises using the action of infrared rays - Kołodyńska, Gabriela; Sieroń, Adrian (Journal of Education, Health and Sport, 2019)
Introduction. Infrared radiation is invisible electromagnetic radiation with a wavelength of 000 nm 770-15. There are many scientific reports, which confirm the positive effect of the therapy waves with a range of red and infrared light both on animals and patients in vivo. Infrared radiation is also used in devices VACU, which are joining the capsule effects of exercise and physical activity infra-red rays. With this combination practitioner achieve extraordinary effectiveness of the therapy. Objective of the work. The aim of this study was to evaluate the effectiveness of training carried out in the capsule Vacu Fit to change the selected anthropometric parameters and body composition parameters. Material and methods.The study was a 27-year old woman, whose age was determined on the metabolic 41 years. During the study of subjective patient he admitted that sports activities practiced occasionally, drinks very little and eats properly. The patient reported the onset of cellulite, stretch marks and excess body fat on the thighs, buttocks and stomach. By joining the training, its aim was to reduce reported problems. Results. After the end of treatment in the majority of parameters assessed changes were observed. Conclusions. A series of trainings conducted in a capsule Vacu alters the anthropometric parameters and body composition